Symbol timing recovery algorithm based on ordered statistic of maximum mean power timing for WBAN - HIYu C; HENLan C; VChao L (Tongxin xuebao)
The symbol timing algorithm based on maximum mean power timing is independent of carrier phase offset,and has the property of capturing timing information fast,which meets the demand of wireless body area networks (WBAN).According to IEEE 802.15.6 standard,the ordered statistic of maximum mean power timing was used to reduce the computational complexity in the symbol timing process.The theoretical analysis and simulation results shows that the proposed algorithm can achieve symbol timing within 32 symbols and reduce the computational complexity by ninety percent at most compared to the original maximum mean power algorithm.The fast synchronization and car-rier-independence property of the proposed algorithm can also make room for carrier-offset recovery and frame synchro-nization.